Let's explore spending money eaudiobook - Waxman, Laura Hamilton (Bumba Books — A First Look at Money., 2019)
What is money and how do we use it? Simple text and fun photos compare the different kinds of things people buy. Critical-thinking questions encourage readers to think further about money and its uses.